Conductive cotton by in situ laccase-polymerization of aniline - Su, Jing (2018)
Conductive cotton fabrics were obtained via in situ aniline polymerization by laccase from Myceliophthora thermophila under mild reaction conditions without the addition of strong proton acids. The reactions were conducted using two types of reactors, namely a water bath (WB) and an ultrasonic bath (US), and the role of a mediator, 1-hydroxybenzotriazol (HBT), on the laccase-assisted polymerization of aniline was investigated. A similar polymerization degree was obtained when using both reactors—however, the ultrasonic bath allowed the experiments to be conducted in shorter periods of time (24 h for WB vs. 2 h for US). The data obtained also revealed that the mediator (1-hydroxybenzotriazol-HBT) played a crucial role in aniline oxidation. A higher conversion yield and polymerization degree were obtained when the reaction was conducted in the presence of this compound, as confirmed by MALDI-TOF analysis. The cotton fabrics coated with polyaniline presented deep coloration and conductivity, especially when the mediator was included on the reactional system. The results obtained are a step forward in the enzymatic polymerization of aniline with the purpose of obtaining coloured conductive textile surfaces, with potential applications in wearable electronics.